1995
DOI: 10.1677/joe.0.1450291
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Di-iodo-l-thyronine suppresses TSH in rats in vivo and in rat pituitary fragments in vitro

Abstract: 3,5-Di-iodo-L-thyronine (T2) is a naturally occurring metabolite of thyroxine (T4). Contrary to earlier findings, T2 has recently been shown to have rapid effects in rat liver and in mononuclear blood cells. In the experiments described here, T2 was tested to determine whether it has a TSH suppressive effect in rats in vivo and in rat pituitary fragments in vitro. In experiments over 2 weeks in rats in vivo, low doses of T2 (20-200 micrograms/100 g body weight per day) had no significant influence on body and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
6
20
1
Order By: Relevance
“…However, we show that at in vivo doses of T 2 and T 3 resulting in equivalent induction of ME gene expression, T 2 is significantly less potent in suppressing plasma TSH. These data would suggest that, in vivo, although capable of suppressing TSH, T 2 does not have selective central thyromimetic activity, in fact being better at inducing hepatic ME gene expression than suppressing TSH (Horst et al 1995). The reasons for the discrepancy between the data from the present study and those from Horst et al are not clear.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…However, we show that at in vivo doses of T 2 and T 3 resulting in equivalent induction of ME gene expression, T 2 is significantly less potent in suppressing plasma TSH. These data would suggest that, in vivo, although capable of suppressing TSH, T 2 does not have selective central thyromimetic activity, in fact being better at inducing hepatic ME gene expression than suppressing TSH (Horst et al 1995). The reasons for the discrepancy between the data from the present study and those from Horst et al are not clear.…”
Section: Discussioncontrasting
confidence: 88%
“…Previous data have indicated that T 2 is capable of suppressing plasma TSH at doses that do not produce significant peripheral effects and, moreover, have shown T 2 to have selective central effects relative to T 3 (Horst et al 1995). Our data confirm the selective thyromimetic activity of T 2 in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In particular, this link is in accordance with animal studies showing that 3,5-T2 was only a third as potent as T3 in suppressing TSH concentrations, and rather high pharmacological 3,5-T2 concentrations are required for TSH suppression (34)(35)(36). However, several animal studies in rodents and other species, for example killifish, indicated that 3,5-T2 interferes with the hypothalamus-pituitary-thyroid axis at several levels such as pituitary, thyroid, and peripheral action, thereby displaying a broad spectrum of mechanisms involved such as classical interaction with TR and also rapid effects at the cell membrane and mitochondria (10,12,14,(34)(35)(36)(37)(38)(39)(40) (for a review, see (3)). Action of 3,5-T2 via these different targets and molecular mechanisms might occur at different 3,5-T2 concentrations and depend on acute or chronic exposure (35,37,40), thus possibly explaining the unexpected bell-shaped relationship with serum TSH.…”
Section: Discussionsupporting
confidence: 85%
“…But in contrast to these beneficial effects, an undesired negative feedback inhibition of the hypothalamuspituitary-thyroid (HPT) axis accompanied by increased heart weight was observed at the dose effectively improving hepatic lipid metabolism and systemic lipid status (Jonas et al 2014). Such observations on doserelated thyromimetic actions, among others also on the pituitary and the heart, are in agreement with published results on mice and rats treated with 3,5-T 2 (Horst et al 1995, Goldberg et al 2012, Padron et al 2014.…”
Section: Introductionsupporting
confidence: 87%